Bagaimana Dinasti Al-Muwahidun Hancur?: Merefleksikan Pemikiran Sejarah Ibn Khaldun - Muhammad Zailani Putra Zailani Putra; Abubakar HM (Syams, 2020)
This article explores Ibn Khaldun’s historical thoughts regarding the causes of the collapse of the Al-Muwahidun Caliphate. The author uses data sources consisting of primary sources and secondary sources obtained through library research. The historical methods used are heuristics (data collection), verification (source criticism), interpretation (data interpretation), and historiography (history writing). The article concludes that humans as social beings cannot live alone. He will establish interactions with other social beings, from the social and political realities of this society that Ibn Khaldun ordained as ‘Ashabiah. The dynasty or the state was formed because of the existence of 'Ashabiah who safely enjoyed the results of development after several generations, an increasingly advanced economy made Al-Muwahidun the dynasty abundant with wealth little by little the nomadic life that became the character of the brand.a became changed like city livelihood. This generation is the one who changed them. This luxury then creates a wasteful and lazy nature. Waste in pursuit of a culture of luxury living makes a country or dynasty try to cover its lack of spending. In addition, power is up for grabs. The king or the Caliph finally crushed their leaders so that there was no power struggle and the dynasty gradually weakened. Some regions do not even trust the center in managing the government, they want the authority to manage the regions themselves. A dynasty that was truly headed for destruction after going through two stages of destruction, namely the army and militia, as well as economic destruction. The factors that led to the collapse of a dynasty were the centralization of power in a person, rampant luxury, as well as the laziness and cowardice that arose from the third generation, as well as the control of the space of power and abuse carried out within the Al-Muwahidun dynasty and the existence of dangerous offensive actions. a dynasty that caused its destruction.